Occupations of citizenship : the missing layer in empowered engagement between rural people with disabilities and primary healthcare workers in South Africa - Sherry, Kate (Department of Public Health and Family Medicine, 2016)
Background: People with disabilities in impoverished rural areas of South Africa struggle to access healthcare, despite the right to health established by the Constitution and the United Nations Convention on the Rights of Persons with Disabilities. Health system challenges and structural conditions of poverty impact this group in specific ways, with implications for households and communities that are not well understood. To date, health systems research and design have largely omitted disability considerations. Primary health care (PHC) calls for community engagement with health systems, to voice local needs, influence service provision, and hold providers to account. However, current models of community engagement rely on certain political, social and economic conditions, which are not present for rural people with disabilities in South Africa. Purpose: This study sought to understand the existing engagement between rural people with disabilities and healthcare workers in the PHC interface, and thus to theorise how this could be strengthened for more responsive and equitable services.